Rules and Regulations for the Investment Account. - International Monetary Fund. Finance Dept. (Washington, D.C. : International Monetary Fund, 2019)
Rules and Regulations for the Investment Account, which were adopted on January 23, 2013 and amended thereafter, were further amended on May 13, 2019 by the Executive Board of the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet